Hypoxia and Human Diseases 2017
DOI: 10.5772/65646
|View full text |Cite
|
Sign up to set email alerts
|

The HIF System Response to ESA Therapy in CKD‐Anemia

Abstract: Anemia is a common complication of chronic kidney disease (CKD) associated with disease progression and increased mortality. This anemia is mainly due to inadequate production of erythropoietin (EPO) by the failing kidneys, resulting from the reduction in renal EPO-producing cells (REPC) or from dysregulation of the hypoxia-inducible factor (HIF) system that regulates several genes related to hypoxia, angiogenesis, fibrosis and glucose metabolism, among others. In this chapter, we present a review on the HIF s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 102 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…It was also shown that the final Moreover, extensive crosstalk between HIF and two master regulators of the inflammatory response, NF-κB and the signal transducer and activator of transcription 3 (STAT3), has been reported [108,116,117]. Under hypoxic conditions, canonical NF-κB signaling activates HIF-1α through the interactions between p50 and p65 subunits and responsive elements in the promoter of the HIF-1α gene [118]. The crosstalk between HIF-1α and NF-κB signaling during senescence has been investigated in several contexts, and its role in orchestrating SASP is widely accepted in atherosclerotic plaques.…”
Section: Hif and Atherosclerosismentioning
confidence: 99%
“…It was also shown that the final Moreover, extensive crosstalk between HIF and two master regulators of the inflammatory response, NF-κB and the signal transducer and activator of transcription 3 (STAT3), has been reported [108,116,117]. Under hypoxic conditions, canonical NF-κB signaling activates HIF-1α through the interactions between p50 and p65 subunits and responsive elements in the promoter of the HIF-1α gene [118]. The crosstalk between HIF-1α and NF-κB signaling during senescence has been investigated in several contexts, and its role in orchestrating SASP is widely accepted in atherosclerotic plaques.…”
Section: Hif and Atherosclerosismentioning
confidence: 99%